PENGARUH FREE CASH FLOW, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG - Nanda Luthfi Fauziah; Dewi Rejeki (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to empirically prove the effect of free cash flow, institutional leadership, managerial leadership and company growth on debt policy in property and real estate and building construction sector companies listed on the Indonesia Stock Exchange in 2017-2019. The sample used is 24 companies with a total population of 72. The method used in this study is a quantitative method with a purposive sampling technique. The data analysis used by the author in this study is Descriptive Statistical Analysis and Multiple Linear Regression Analysis. The results of the study prove that partially Free Cash Flow, Institutional Ownership, and Managerial Ownership have an effect on Debt Policy. Meanwhile, the Company's growth has no effect on the Debt Policy. But simultaneously, simultaneously Free Cash Flow, Institutional Ownership, Managerial Ownership, and Company Growth together affect the Debt Policy